ANALISIS USAHA HOME INDUSTRI TEMPE DI KAMPUNG UNGGULAN TEMPE KELURAHAN TENGGILIS MEJOYO KECAMATAN TENGGILIS MEJOYO KOTA SURABAYA - Liantono, Aris; Suparta, I Made (JEB17 : Jurnal Ekonomi dan Bisnis, 2021)
This research is about the tempe home industry business in Tenggilis Mejoyo Village, Tenggilis Mejoyo District, Surabaya City with the title "Analysis of Tempe Home Industry Business in Tempe Superior Village, Tenggilis Mejoyo Village, Tenggilis Mejoyo District, Surabaya City". As for the research area, the selected Tempe Village is Tenggilis Mejoyo Village because in that area there are many tempe entrepreneurs. This study aims to describe and analyze the profile of the tempe-making business in Tempe Superior Village, Tenggilis Mejoyo District, Surabaya City. This study uses qualitative methods and uses interviews and observations as primary data collection tools. This study uses the Revenue Cost Ratio and Return Of Investment as an indicator of the feasibility of making tempeh. Data were obtained from 5 informants of tempe business owners. The results are based on research that has been done that the tempe-making business they run is quite long around 16-30 years. The amount of tempeh also varies, with the minimum being 14,000 seeds/month and the maximum being 50,000 seeds/month. The price of the tempeh they sell is around Rp. 1,750 – Rp. 2,000. The tempe-making business itself produces an ROI that is quite by the average monthly capital issued of Rp. 39.661.500/month which produces an average ROI of 16,76% and produces an average R/C of 1,17 which means > 1, thus the average business of making tempeh in Tempe Superior Village, Tenggilis Mejoyo District, Surabaya City is profitable.